The Learning Evaluation of Business Incubator's Role in Developing Technology-Based Startups at Technology Business Incubator - Ghina, Astri; Sinaryanti, Ina (The Asian Journal of Technology Management (AJTM), 2021)
Abstract. Technology-based startup plays a vital role in improving the Indonesian economy. There are thousands of units of technology-based startups, though most of them are not adequately sustainable. The inadequacy is attributed to the fact that the products or services created are not in line with market needs and do not help understand business processes. Universities play an essential role in developing startups through business incubators to compete in the digital age. There is no conducive learning environment for business incubators in Indonesia, though the national standards are used. This research evaluates the learning process in a Technology Business Incubator in Bandung University using case study methods. Data is collected by performing in-depth interviews with three incubator managers and seven startup founders or tenants who have completed the incubation process. The business industry consists of education, design, printing, and fishery, while the interviews cover the process before, during, and after incubation, including the tenant's selection criteria and stages, learning processes in incubators and facilities, after graduation programs, and measurement of the impacts. The results show that the practices fit the ideal conditions, including training-focused and knowledge sharing session programs or skills, knowledge provisions, and expertise improvement programs for tenants, rental system facilities for graduates, and commercialization support. Furthermore, there are opportunities to improve several aspects, including developing tenant admission selection criteria, effective learning approaches, coaching, networking, and broader funding, graduation criteria, monitoring for graduates, and a more comprehensive range of impact measurement. This research helps guide business incubators to prioritizedeveloping aspects of services. Moreover, evaluation using the mixed method is open for further investigation.                                                                                                                                  Keywords:  Business Incubator, Pre-incubation, Main incubation, Post-incubation, Startup, Learning Evaluation